2018
DOI: 10.1186/s13036-018-0122-7
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Tissue Engineering and Regeneration

Abstract: The lymphatic system is a major circulatory system within the body, responsible for the transport of interstitial fluid, waste products, immune cells, and proteins. Compared to other physiological systems, the molecular mechanisms and underlying disease pathology largely remain to be understood which has hindered advancements in therapeutic options for lymphatic disorders. Dysfunction of the lymphatic system is associated with a wide range of disease phenotypes and has also been speculated as a route to rescue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 268 publications
(443 reference statements)
1
54
0
Order By: Relevance
“…Nonetheless, the importance of a sufficient lymphatic network for optimal tissue metabolism and an intact immune response must not be underestimated. The main function of the lymphatic vasculature is interstitial fluid drainage [5], which is important for fluid homeostasis, immune cell surveillance and trafficking, and lipid absorption [5][6][7][8][9][10]. In inflammatory settings, lymphangiogenesis facilitates the resolution of tissue edema and promotes macrophage and dendritic cell mobilization [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the importance of a sufficient lymphatic network for optimal tissue metabolism and an intact immune response must not be underestimated. The main function of the lymphatic vasculature is interstitial fluid drainage [5], which is important for fluid homeostasis, immune cell surveillance and trafficking, and lipid absorption [5][6][7][8][9][10]. In inflammatory settings, lymphangiogenesis facilitates the resolution of tissue edema and promotes macrophage and dendritic cell mobilization [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In inflammatory settings, lymphangiogenesis facilitates the resolution of tissue edema and promotes macrophage and dendritic cell mobilization [11][12][13][14]. If the local immune response is delayed, or interstitial edema reduces cellular gas exchange and nutrition (by increasing diffusion distance), the wound healing process is ultimately impaired [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The lymphatic system works synergistically with the blood microvasculature in maintaining the various organs in the body and is one of the vasculature components that should be included in tissueengineered models in the future. 105 Although the lymphatic vasculature has not been the primary focus of this review, many of the models and techniques shown here for blood microvasculature formation may also be used for lymphatic vasculature. However, additional modifications, such as changing the type of matrices, may need to be made when incorporating lymphatic ECs in tissue-engineered models.…”
Section: Discussionmentioning
confidence: 99%
“…This model could additionally be interrogated to better understand how bone marrow mesenchymal stem cells contribute to metastasis by angiogenesis. 129 Techniques, including cell sheet engineering and coculture systems, which have been used to engineer vasculature can similarly be applied to the lymphatic field, in the way that Marino et al successfully engineered prevascularized dermoepidermal human skin grafts containing lymphatic capillaries. 130 Alimperti et al developed a vessel-on-a-chip with perfused endothelialized channels to mimic the barrier function of the vasculature and recapitulate the endothelial barrier between circulating blood and tissue.…”
Section: Engineering Vasculature and Lymphaticsmentioning
confidence: 99%